B1-grade cable material as well as preparation method and application thereof

By using a specific ratio of matrix resin, flame retardant, smoke inhibitor, charcoal and silane coupling agent in the B1 cable material, the problem that the B1 cable material in the prior art is difficult to meet the requirements of high flame retardant performance, low smoke output and low toxicity at the same time, and excellent flame retardant effect and combustion performance are achieved.

CN119684704APending Publication Date: 2025-03-25HEBEI SHANGHUA NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510026777.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing B1-level cable materials are difficult to meet the requirements of high flame retardant performance, low smoke output and low toxicity at the same time, and there are technical difficulties in the selection of cable insulation, cable structure and sheath materials.

Method used

The raw materials such as matrix resin, flame retardant, smoke-resisting charcoal-forming agent and silane coupling agent with specific ratios are used to form excellent charcoal-forming crust effect and flame retardant performance through composite strengthening.

Benefits of technology

It achieves excellent flame retardant effect of B1 cable material, meets the B1 combustion performance requirements of GB/T 31247, including no combustion drips and particles, reducing flame spread and heat release rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of cable coating materials, and particularly discloses a B1-grade cable material as well as a preparation method and application thereof. The cable material provided by the invention comprises matrix resin, a compatilizer, a flame retardant, a lubricant, an antioxidant, a smoke suppression charring agent, nano silicon dioxide and a silane coupling agent, the matrix resin is a mixture of linear low density polyethylene resin, an ethylene-octylene copolymer, metallocene polyethylene and an ethylene-vinyl acetate copolymer; the flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite; the smoke suppression charring agent is a mixture of hydrous magnesium silicate and modified montmorillonite; the silane coupling agent is a mixture of vinyl silane and diamino silane. According to the cable material provided by the invention, the specific matrix resin, the flame retardant, the smoke suppression charring agent and the silane coupling agent are combined with auxiliaries such as the compatilizer, the lubricant, the antioxidant and the nano silicon dioxide to serve as raw materials, so that the flame-retardant effect of the B1-grade cable material is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cable coating materials, and in particular to a B1-class cable material and a preparation method and application thereof. Background Art

[0002] According to the relevant provisions of the new version of the civil building electrical fire protection design standard DG / TJ08-2048-2024, for buildings with a height greater than 250m and a building area greater than 250,000m 2 Cables used in high-rise public buildings, schools, hospitals, kindergartens, nurseries, and elderly care facilities should meet the requirements of GB / T31247-2014 "Classification of Combustion Performance of Electrical Cables and Optical Cables", with a combustion performance of B1, burning drips / particles of d0, smoke toxicity of t0, and corrosiveness of A1.

[0003] B1-class cables have high flame retardant performance requirements. They must meet strict flame retardant standards such as short flame spread distance and fast self-extinguishing time under specified conditions. This means that flame retardants and other additives must be accurately proportioned in the selection of cable sheath materials to ensure sufficient flame retardant effect while not affecting the original electrical and mechanical properties of the cable too much. Therefore, finding this balance is one of the difficulties. Secondly, B1-class cables require low smoke and low toxicity when burned, especially d0 level (no burning drops / particles within 1200s). At present, it is difficult to achieve this by simply adjusting the B1-class cable material formula. It is also necessary to perform special treatment and screening on the cable insulation, cable structure, and sheath materials to ensure that the core structure and the sheath can achieve a complementary effect. A slight deviation in the core structure selection may affect the overall performance of the cable when it burns. Therefore, manufacturing suitable B1-class cable materials and matching them with suitable cable structures have become technical difficulties in manufacturing B1-class standard cables. Summary of the invention

[0004] In view of the above problems, the present invention provides a B1-class cable material and a preparation method and application thereof.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is: The first aspect of the present invention provides a B1-class cable material, comprising the following raw material components in percentage by weight: 15%-30% of base resin, 4%-8% of compatibilizer, 50%-70% of flame retardant, 1%-3% of lubricant, 0.3%-1% of antioxidant, 3%-8% of smoke suppressant and carbonizing agent, 3%-8% of nano-silicon dioxide and 1%-5% of silane coupling agent; Wherein, the base resin is a mixture of linear low-density polyethylene resin, ethylene-octene copolymer, metallocene polyethylene and ethylene-vinyl acetate copolymer; The flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite; The smoke suppressant and charring agent is a mixture of hydrous magnesium silicate and modified montmorillonite, and the modified montmorillonite is montmorillonite modified by quaternary ammonium salt and polyethylene glycol; The silane coupling agent is a mixture of vinyl silane and bisaminosilane.

[0006] Compared with the prior art, the cable material matrix resin provided by the present invention selects linear low-density polyethylene resin, ethylene-octene copolymer, metallocene polyethylene and ethylene-vinyl acetate copolymer as the composite matrix resin; wherein the linear low-density polyethylene resin and the metallocene polyethylene will produce a crystalline region during combustion, which can serve as a physical barrier to slow down the transfer of heat and oxygen, thereby achieving a flame retardant effect; the flexible polymer chains in the ethylene-octene copolymer and the ethylene-vinyl acetate copolymer can undergo conformational changes during the combustion process and then interweave to form a tight carbon layer, thereby reducing heat release and achieving a flame retardant effect; Ethylene-octene copolymer, ethylene-vinyl acetate copolymer, linear low-density polyethylene resin and metallocene polyethylene have a synergistic effect to form a more stable and continuous carbon layer structure, thereby improving the flame retardant effect. In addition, ethylene-octene copolymer can also improve the processing fluidity of other base resins, so that the base resin and other additives can be better mixed and evenly improved, thereby improving the overall performance of the cable material. Ethylene-vinyl acetate copolymer enhances its compatibility with other base resins through its polar groups, promotes the synergistic effect of each component, and is conducive to forming a uniform carbon layer, avoiding burning drippings, and improving the flame retardant effect.

[0007] Vinyl silane and bisaminosilane can undergo condensation polymerization under combustion conditions to form a stable cross-linked network structure. This cross-linked network structure can penetrate the carbon layer formed by the matrix resin during combustion, and enhance the stability of the carbon layer by limiting the movement of the molecular chain of the matrix resin; and the specific content of silicon in the silane coupling agent can also promote the graphitization of the carbon layer during combustion, and improve the thermal stability of the carbon layer so that the carbon layer can better block heat and oxygen, prevent the spread of flames, improve flame retardant efficiency, and enhance flame retardant effect; some functional groups in specific silane coupling agents can also chemically bond with the matrix resin, improve the interfacial bonding force between the matrix and the resin, and better fix other additives in the cable material, thereby improving the flame retardant performance; and specific silane coupling agents can also reduce the burning speed of the cable material and inhibit the dripping of combustion products by forming a protective film on the surface of the cable material and increasing the viscosity of the material to improve the flame retardant effect.

[0008] During the combustion process, aluminum hydroxide in the flame retardant first decomposes to produce water vapor and absorb heat, which prevents the combustion of combustibles to a certain extent. When the temperature rises further, magnesium hydroxide begins to decompose at the same time to produce water vapor and absorb heat. The combination of the two forms a gradient flame retardant, which greatly improves the flame retardant effect of the cable material; hydrotalcite releases water and carbon dioxide when heated, which dilutes the concentration of combustible gases to a certain extent and reduces the temperature of the combustion area. The metal ions in its layered structure can also combine with the functional groups in the silane coupling agent to improve the flame retardant effect by improving the stability of the carbon layer structure; the three flame retardants of magnesium hydroxide, aluminum hydroxide and hydrotalcite work synergistically to form a more effective barrier layer during combustion, thereby improving the flame retardant effect of the cable material; magnesium hydroxide, aluminum hydroxide and hydrotalcite, three flame retardants with different crystal structures, are used in combination to achieve the crystal complementary effect of the flame retardant powder, and the different chemical composition differences can effectively make up for the problem of low flame retardant efficiency of a single hydroxide.

[0009] The present invention selects a mixture of hydrated magnesium silicate and modified montmorillonite as a smoke suppressant and charring agent, wherein the special structure of the hydrated magnesium silicate can form a physical barrier layer on the surface of the material during the combustion process, thereby preventing heat and oxygen from being transferred to the interior of the cable material, thereby improving the flame retardant effect; the quaternary ammonium salt and polyethylene glycol can change the montmorillonite from hydrophilic to lipophilic, so that the modified montmorillonite is evenly dispersed in the matrix of the material, and the quaternary ammonium salt can react with the functional groups of the matrix resin, so that the resin molecules are cross-linked in the interlayer structure and surface of the modified montmorillonite, thereby improving the strength of the char layer and achieving an excellent flame retardant effect; the nano silicon dioxide can react with the metal oxide generated after the flame retardant in the flame retardant is burned to generate silicate under high temperature conditions, further enhancing the strength of the char layer and improving the flame retardant effect.

[0010] The B1-class cable material provided by the present invention selects specific base resin, flame retardant, smoke suppressant and charring agent and silane coupling agent and combines the compatibilizer, lubricant, antioxidant and nano-silica and other auxiliary agents provided by the present invention as raw materials, and each component plays a composite reinforcement role, so that the B1-class cable material has excellent charring and crusting effect, and also greatly improves the flame retardant effect of the B1-class cable material.

[0011] Preferably, the mass ratio of ethylene-vinyl acetate copolymer, ethylene-octene copolymer, metallocene polyethylene and linear low-density polyethylene resin in the matrix resin is (4-7): (3-5): (6-8): (10-16).

[0012] The preferred matrix resin and the content thereof limited within a certain ratio range are beneficial to further improving the flame retardant effect of the cable material.

[0013] Preferably, the linear low-density polyethylene resin has a melt flow rate of 1 g / 10 min-3 g / 10 min, a tensile strength of 25 MPa-27 MPa, and an elongation at break of 775%-785%.

[0014] Further preferably, the linear low-density polyethylene resin is Borealis FB2230.

[0015] Preferably, the melt flow rate of the ethylene-octene copolymer is 1.2 g / 10 min-1.6 g / 10 min, the tensile strength is 7 MPa-9 MPa, and the elongation at break is 1190%-1210%.

[0016] Further preferably, the ethylene-octene copolymer is ExxonMobil 5371.

[0017] Preferably, the metallocene polyethylene has a melt flow rate of 1.26 g / 10 min-1.30 g / 10 min, a tensile strength of 38 MPa-42 MPa, and an elongation at break of 725%-735%.

[0018] More preferably, the metallocene polyethylene is ExxonMobil 3518.

[0019] Preferably, the vinyl acetate mass content of the ethylene-vinyl acetate copolymer is 25-28%, the melt flow rate is 5g / 10min-7g / 10min, the tensile strength is 24MPa-27MPa, and the elongation at break is 942%-945%.

[0020] Further preferably, the ethylene-vinyl acetate copolymer is Zhejiang Petrochemical V6110M.

[0021] Preferably, the compatibilizer is maleic anhydride grafted ethylene-octene copolymer.

[0022] Further preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted ethylene-octene copolymer is 0.8%-2%.

[0023] Further preferably, the maleic anhydride grafted ethylene-octene copolymer is Jiangsu Jiuju Polymer 1241.

[0024] Preferably, the mass ratio of magnesium hydroxide, aluminum hydroxide and hydrotalcite in the flame retardant is (2-4): (1-3): (15-30).

[0025] The present invention further limits the ratio of magnesium hydroxide, aluminum hydroxide and hydrotalcite in the flame retardant, so that the three flame retardant materials can further achieve a synergistic effect and improve the flame retardant effect of the cable material.

[0026] Preferably, the lubricant is a mixture of maleic anhydride grafted polyethylene wax and ethylene bisstearamide.

[0027] Further preferably, the mass ratio of maleic anhydride grafted polyethylene wax to ethylene bisstearamide in the lubricant is 1:(3-5).

[0028] Preferably, the antioxidant is a polyhedral hindered phenol antioxidant.

[0029] More preferably, the antioxidant is BASF 1010 from Germany.

[0030] Preferably, the mass ratio of hydrous magnesium silicate to modified montmorillonite in the smoke suppressant and charring agent is 1:(3-5).

[0031] Preferably, the preparation method of the modified montmorillonite comprises the following steps: S1, adding montmorillonite to an ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding the quaternary ammonium salt to an ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and quaternary ammonium salt solution to the hydrochloric acid aqueous solution, then adding polyethylene glycol, reacting at 80° C.-82° C., filtering, washing, and drying to obtain modified montmorillonite.

[0032] The preparation method of the modified montmorillonite provided by the invention is simple in modification method, and the montmorillonite is modified from hydrophilic to lipophilic by using quaternary ammonium salt and polyethylene glycol, so that the modified montmorillonite is evenly dispersed in the cable material, thereby improving the flame retardant property of the cable material.

[0033] Preferably, in S1, the mass volume ratio of the montmorillonite to the ethanol aqueous solution is 110 g: (1-1.1) L, and the volume content of the ethanol aqueous solution is 50%-52%.

[0034] Preferably, in S2, the quaternary ammonium salt is hexadecyltrimethylammonium bromide.

[0035] The preferred quaternary ammonium salt is beneficial to further improve the modification effect of montmorillonite, thereby improving the flame retardant effect of the cable material.

[0036] Preferably, in S2, the mass volume ratio of the quaternary ammonium salt and the ethanol aqueous solution is (50-52) g: (200-210) mL, and the volume content of the ethanol aqueous solution is 50%-52%.

[0037] Preferably, in S3, the mass ratio of the montmorillonite to the quaternary ammonium salt is 110:(50-52).

[0038] The preferred amount of quaternary ammonium salt is beneficial to improving the flame retardant properties of the cable material by improving the modification effect of montmorillonite.

[0039] Preferably, in S3, the mass volume ratio of the montmorillonite and the hydrochloric acid aqueous solution is 110 g: (30-35) mL, wherein the concentration of the hydrochloric acid aqueous solution is 1 mol / L-1.1 mol / L.

[0040] Preferably, in S3, the mass ratio of montmorillonite to polyethylene glycol is 11:(1-1.2).

[0041] The preferred amount of polyethylene glycol is beneficial to improving the flame retardant properties of the cable material by improving the modification effect of montmorillonite.

[0042] Preferably, in S3, the reaction time is 4h-5h.

[0043] Preferably, in S3, the particle size of the modified montmorillonite is 20nm-50nm.

[0044] Preferably, the mass ratio of vinyl silane to bisaminosilane in the silane coupling agent is 1:(0.5-0.7).

[0045] The present invention further limits the usage ratio of vinyl silane and bisaminosilane in the silane coupling agent, which is beneficial to further improve the flame retardant effect of the cable material.

[0046] More preferably, the model of the vinyl silane is SICO-V010.

[0047] More preferably, the model of the bisaminosilane is SICO-ANP26.

[0048] The second aspect of the present invention provides a method for preparing the above-mentioned B1-grade cable material, comprising the following steps: The weighed base resin, compatibilizer, flame retardant, lubricant, antioxidant, smoke suppressant, carbon forming agent, nano-silica and silane coupling agent are reacted at 160° C.-180° C., and then extruded through a twin-screw extruder and a single-screw extruder in sequence, and cooled to obtain a B1 grade cable material.

[0049] Preferably, the reaction time is 10 min-15 min.

[0050] Preferably, the extrusion temperature of the twin-screw extruder is 110°C in zone 1, 120°C in zone 2, 125°C in zone 3, 125°C in zone 4, 130°C in zone 5, 135°C in zone 6, 135°C in zone 7, and 135°C in zone 8.

[0051] Preferably, the extrusion temperature of the single screw extruder is 100° C. in zone 1, 110° C. in zone 2, 120° C. in zone 3, 125° C. in zone 4, and 130° C. in zone 5.

[0052] A third aspect of the present invention provides a Class B1 cable, wherein the structure of the Class B1 cable comprises, from the inside to the outside, a conductor layer, an insulating layer, a filling layer, a wrapping layer and a cable sheath.

[0053] Preferably, the conductor layer is a copper core or an aluminum core.

[0054] Further preferably, the cross-sectional area of ​​the conductor layer is 2.5 mm 2 .

[0055] Preferably, the insulating layer is the B1 grade cable material.

[0056] Further preferably, the thickness of the insulating layer is 0.7 mm-0.8 mm.

[0057] Preferably, the filling layer is a flame-retardant braided polypropylene rope.

[0058] Preferably, the diameter of the polypropylene flame-retardant braided rope in the filling layer is 0.7 mm-0.8 mm.

[0059] Preferably, the wrapping layer is a low-smoke, halogen-free, flame-retardant and fire-resistant wrapping tape or a glass fiber wrapping tape.

[0060] Preferably, the thickness of the low-smoke, halogen-free, flame-retardant and fire-resistant wrapping tape or the glass fiber wrapping tape in the wrapping layer is 0.2 mm.

[0061] Preferably, the material of the cable sheath is the B1 grade cable material.

[0062] Preferably, the thickness of the cable sheath is 1.2 mm-2.5 mm. DETAILED DESCRIPTION

[0063] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0064] In order to better illustrate the present invention, further examples are given below.

[0065] Example 1 This embodiment provides a B1-grade cable material, which includes the following raw material components in percentage by mass: 15% base resin, 8% Jiangsu Jiuju Polymer 1241, 64% flame retardant, 1% lubricant, 1% German BASF 1010, 3% smoke suppression and carbonization agent, 3% nano-silicon dioxide and 5% silane coupling agent; The base resin is a mixture of Zhejiang Petrochemical V6110M, ExxonMobil 5371, ExxonMobil 3518 and Borealis FB2230 in a mass ratio of 7:5:6:10; The flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite in a mass ratio of 2:1:30; The lubricant is a mixture of maleic anhydride grafted polyethylene wax and ethylene bisstearamide in a mass ratio of 1:3; The silane coupling agent is a mixture of vinyl silane and bisamino silane in a mass ratio of 1:0.5; A mixture of hydrous magnesium silicate and modified montmorillonite in a mass ratio of 1:5 as a smoke suppressant and charring agent; The preparation method of modified montmorillonite comprises the following steps: S1, adding 110g of montmorillonite to 1L of 50% by volume ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding 50g of hexadecyltrimethylammonium bromide to 200mL of 52% by volume ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and the quaternary ammonium salt solution to 30 mL of a 1 mol / L hydrochloric acid aqueous solution, then adding 10 g of polyethylene glycol, reacting at 80° C. for 4 h, filtering, washing, and drying to obtain a modified montmorillonite with a particle size of 20 nm; This embodiment also provides a method for preparing a B1-grade cable material, comprising the following steps: The weighed base resin, Jiangsu Jiuju Polymer 1241, flame retardant, lubricant, German BASF 1010, smoke suppressant and carbonizing agent, nano-silica and silane coupling agent were reacted at 180°C for 10 minutes, then extruded through a twin-screw extruder, then extruded through a single-screw extruder, and cooled to obtain a B1-grade cable sheath material; The extrusion temperature of the twin-screw extruder is 110°C in zone 1, 120°C in zone 2, 125°C in zone 3, 125°C in zone 4, 130°C in zone 5, 135°C in zone 6, 135°C in zone 7, and 135°C in zone 8.

[0066] The extrusion temperature of the single screw extruder is 100°C in zone 1, 110°C in zone 2, 120°C in zone 3, 125°C in zone 4, and 130°C in zone 5.

[0067] Example 2 This embodiment provides a B1-grade cable material, which includes the following raw material components in percentage by mass: 30% base resin, 14% Jiangsu Jiuju Polymer 124, 49% flame retardant, 3% lubricant, 0.3% German BASF 1010, 8% smoke suppression and carbonization agent, 3% nano-silicon dioxide and 2.7% silane coupling agent; The base resin is a mixture of Zhejiang Petrochemical V6110M, ExxonMobil 5371, ExxonMobil 3518 and Borealis FB2230 in a mass ratio of 4:3:8:16; The flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite in a mass ratio of 4:3:15; The lubricant is a mixture of maleic anhydride grafted polyethylene wax and ethylene bisstearamide in a mass ratio of 1:5; The silane coupling agent is a mixture of vinyl silane and bisamino silane in a mass ratio of 1:0.7; A mixture of hydrous magnesium silicate and modified montmorillonite in a mass ratio of 1:3 as a smoke suppressant and charring agent; The preparation method of modified montmorillonite comprises the following steps: S1, adding 110g of montmorillonite to 1.1L of 52% by volume ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding 52g of hexadecyltrimethylammonium bromide to 210mL of 50% by volume ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and the quaternary ammonium salt solution to 35 mL of a 1.1 mol / L hydrochloric acid aqueous solution, then adding 12 g of polyethylene glycol, reacting at 82° C. for 5 h, filtering, washing, and drying to obtain a modified montmorillonite with a particle size of 50 nm; This embodiment also provides a method for preparing a B1-grade cable material, comprising the following steps: The weighed base resin, Jiangsu Jiuju Polymer 1241, flame retardant, lubricant, German BASF 1010, smoke suppressant and carbonizing agent, nano-silica and silane coupling agent were reacted at 160° C. for 15 min, then extruded through a twin-screw extruder, then extruded through a single-screw extruder, and cooled to obtain a B1-grade cable sheath material; The extrusion temperature of the twin-screw extruder is 110°C in zone 1, 120°C in zone 2, 125°C in zone 3, 125°C in zone 4, 130°C in zone 5, 135°C in zone 6, 135°C in zone 7, and 135°C in zone 8.

[0068] The extrusion temperature of the single screw extruder is 100°C in zone 1, 110°C in zone 2, 120°C in zone 3, 125°C in zone 4, and 130°C in zone 5.

[0069] Example 3 This embodiment provides a B1-grade cable material, which includes the following raw material components in percentage by mass: 17% base resin, 16% Jiangsu Jiuju Polymer 124, 64% flame retardant, 1.5% lubricant, 1.6% German BASF 1010, 3.9% smoke suppression and carbonization agent, 5% nano-silicon dioxide and 2% silane coupling agent; The base resin is a mixture of Zhejiang Petrochemical V6110M, ExxonMobil 5371, ExxonMobil 3518 and Borealis FB2230 in a mass ratio of 6:4:7:12; The flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite in a mass ratio of 3:2:18; The lubricant is a mixture of maleic anhydride grafted polyethylene wax and ethylene bisstearamide in a mass ratio of 1:4; The silane coupling agent is a mixture of vinyl silane and bisamino silane in a mass ratio of 1:0.6; A mixture of hydrous magnesium silicate and modified montmorillonite in a mass ratio of 1:4 as a smoke suppressant and charring agent; The preparation method of modified montmorillonite comprises the following steps: S1, adding 110 g of montmorillonite to 1.05 L of 51% ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding 51g of hexadecyltrimethylammonium bromide to 205mL of 51% ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and the quaternary ammonium salt solution to 32 mL of a 1.05 mol / L hydrochloric acid aqueous solution, then adding 11 g of polyethylene glycol, reacting at 81° C. for 4.5 h, filtering, washing, and drying to obtain a modified montmorillonite with a particle size of 30 nm; This embodiment also provides a method for preparing a B1-grade cable material, comprising the following steps: The weighed base resin, Jiangsu Jiuju Polymer 1241, flame retardant, lubricant, German BASF 1010, smoke suppressant and carbonizing agent, nano-silica and silane coupling agent were reacted at 170°C for 12 minutes, then extruded through a twin-screw extruder, then extruded through a single-screw extruder, and cooled to obtain a B1-grade cable sheath material; The extrusion temperature of the twin-screw extruder is 110°C in zone 1, 120°C in zone 2, 125°C in zone 3, 125°C in zone 4, 130°C in zone 5, 135°C in zone 6, 135°C in zone 7, and 135°C in zone 8.

[0070] The extrusion temperature of the single screw extruder is 100°C in zone 1, 110°C in zone 2, 120°C in zone 3, 125°C in zone 4, and 130°C in zone 5.

[0071] Comparative Example 1 This comparative example provides a cable material, which is different from Example 1 in that: Zhejiang Petrochemical V6110M is replaced with an equal amount of ExxonMobil 5371; The other operations are the same as those in Example 1.

[0072] Comparative Example 2 This comparative example provides a cable material, which is different from Example 1 in that: hydrotalcite is replaced by an equal amount of brucite; The other operations are the same as those in Example 1.

[0073] Comparative Example 3 This comparative example provides a cable material, which is different from Example 1 in that vinyl silane is replaced by an equal amount of methyl silane coupling agent KH570.

[0074] Comparative Example 4 This comparative example provides a cable material, which is different from Example 1 in that: all magnesium hydroxide is replaced by aluminum hydroxide; The other operations are the same as those in Example 1.

[0075] Comparative Example 5 This comparative example provides a cable material, which is different from Example 1 in that polyethylene glycol is replaced by an equal amount of polycaprolactone Swedish 6550. The specific preparation method of modified montmorillonite includes the following steps: S1, adding 110g of montmorillonite to 1L of 50% by volume ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding 50g of hexadecyltrimethylammonium bromide to 200mL of 52% by volume ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and the quaternary ammonium salt solution to 30 mL of 1 mol / L hydrochloric acid aqueous solution, then adding 10 g of polycaprolactone, reacting at 80° C. for 4 h, filtering, washing, and drying to obtain a modified montmorillonite with a particle size of 20 nm; The other operations are the same as those in Example 1.

[0076] Comparative Example 6 This comparative example provides a cable material, which is different from Example 1 in that hexadecyltrimethylammonium bromide is replaced by an equal amount of octadecyltrimethylammonium chloride 1831. The specific preparation method of the modified montmorillonite comprises the following steps: S1, adding 110g of montmorillonite to 1L of 50% by volume ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding 50g of octadecyltrimethylammonium chloride 1831 to 200mL of 52% ethanol aqueous solution to obtain a first mixed solution; S3, adding the montmorillonite dispersion and the first mixed solution to 30 mL of 1 mol / L hydrochloric acid aqueous solution, then adding 10 g of polyethylene glycol, reacting at 80° C. for 4 h, filtering, washing, and drying to obtain modified montmorillonite with a particle size of 20 nm; The other operations are the same as those in Example 1.

[0077] The cable materials provided in Examples 1-3 and Comparative Examples 1-6 were prepared into cables, and the specific structure was as follows: 2 A layer of cable material is extruded outside the copper conductor as an insulation layer, and the thickness of the insulation layer is 0.7mm; a polypropylene flame-retardant braided rope with a diameter of 0.8mm is twisted and wrapped around the outside of the insulation, and then a low-smoke halogen-free flame-retardant wrapping tape with a thickness of 0.4mm is twisted and overlapped to cover the outer layer; then the manufactured cable material is extruded on the outer layer of the wire core by a single-screw extruder as a cable sheath, and the thickness of the cable sheath is 1.2mm. The cable materials provided in Examples 1-3 and Comparative Examples 1-6 are prepared into cables and tested, wherein the flame spread FS, the peak value of the heat release rate HRR peak value, the total heat release within 1200s of the fire, the combustion growth rate index, the peak value of the smoke rate, and the total smoke production within 1200s of the fire refer to GB / T 31248-2014, the smoke density (minimum light transmittance) refers to GB / T17651.2, and the vertical flame spread refers to GB / T18380-2022. The specific test results are shown in Table 1: Table 1

[0078] As can be seen from Table 1, the B1-class cable material provided in the embodiment of the present invention has excellent charring and crusting effect and excellent flame retardant properties, ultra-low combustion calorific value and heat release rate, and no burning dripping and particles, meeting the B1-class d0 requirements of GB / T 31247, and is conducive to the promotion and use of B1-class cables in fire emergency lines.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A B1 grade cable material, characterized in that: The raw material components include the following mass percentages: base resin 15%-30%, compatibilizer 4%-8%, flame retardant 50%-70%, lubricant 1%-3%, antioxidant 0.3%-1%, smoke suppressant 3%-8%, nano silicon dioxide 3%-8% and silane coupling agent 1%-5%; Wherein, the base resin is a mixture of linear low-density polyethylene resin, ethylene-octene copolymer, metallocene polyethylene and ethylene-vinyl acetate copolymer; The flame retardant is a mixture of magnesium hydroxide, aluminum hydroxide and hydrotalcite; The smoke suppressant and charring agent is a mixture of hydrous magnesium silicate and modified montmorillonite, and the modified montmorillonite is montmorillonite modified by quaternary ammonium salt and polyethylene glycol; The silane coupling agent is a mixture of vinyl silane and bisaminosilane.

2. The B1-level cable material according to claim 1, characterized in that: The mass ratio of ethylene-vinyl acetate copolymer, ethylene-octene copolymer, metallocene polyethylene and linear low-density polyethylene resin in the base resin is (4-7): (3-5): (6-8): (10-16); and / or The compatibilizer is maleic anhydride grafted ethylene-octene copolymer.

3. The B1-level cable material according to claim 1, characterized in that: The mass ratio of magnesium hydroxide, aluminum hydroxide and hydrotalcite in the flame retardant is (2-4): (1-3): (15-30); and / or The lubricant is a mixture of maleic anhydride grafted polyethylene wax and ethylene bisstearamide.

4. The B1 class cable material according to claim 3, characterized in that: The mass ratio of maleic anhydride grafted polyethylene wax to ethylene bisstearamide in the lubricant is 1:(3-5).

5. The B1-level cable material according to claim 1, characterized in that: The antioxidant is a polyhedral hindered phenol antioxidant.

6. The B1-level cable material according to claim 1, characterized in that: The mass ratio of hydrous magnesium silicate to modified montmorillonite in the smoke suppression and charring agent is 1:(3-5); and / or The mass ratio of vinyl silane to bisaminosilane in the silane coupling agent is 1:(0.5-0.7).

7. The B1 class cable material according to claim 1 or 6, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: S1, adding montmorillonite to an ethanol aqueous solution to obtain a montmorillonite dispersion; S2, adding the quaternary ammonium salt to an ethanol aqueous solution to obtain a quaternary ammonium salt solution; S3, adding the montmorillonite dispersion and quaternary ammonium salt solution to the hydrochloric acid aqueous solution, then adding polyethylene glycol, reacting at 80° C.-82° C., filtering, washing, and drying to obtain modified montmorillonite.

8. The B1 class cable material according to claim 7, characterized in that: In S1, the mass volume ratio of the montmorillonite to the ethanol aqueous solution is 110 g: (1-1.1) L, and the volume content of the ethanol aqueous solution is 50%-52%; and / or In S2, the quaternary ammonium salt is hexadecyltrimethylammonium bromide; and / or In S2, the mass volume ratio of the quaternary ammonium salt and the ethanol aqueous solution is (50-52) g: (200-210) mL, and the volume content of the ethanol aqueous solution is 50%-52%.

9. The B1 class cable material according to claim 7 or 8, characterized in that: In S3, the mass ratio of the montmorillonite to the quaternary ammonium salt is 110:(50-52); and / or In S3, the mass volume ratio of the montmorillonite to the hydrochloric acid aqueous solution is 110 g: (30-35) mL, wherein the concentration of the hydrochloric acid aqueous solution is 1 mol / L-1.1 mol / L; and / or In S3, the mass ratio of montmorillonite to polyethylene glycol is 11:(1-1.2); and / or In S3, the reaction time is 4h-5h; and / or In S3, the particle size of the modified montmorillonite is 20nm-50nm.

10. A method for preparing the B1-class cable material according to any one of claims 1 to 9, characterized in that: The steps include: The weighed base resin, compatibilizer, flame retardant, lubricant, antioxidant, smoke suppressant, carbon forming agent, nano-silica and silane coupling agent are reacted at 160° C.-180° C., and then extruded through a twin-screw extruder and a single-screw extruder in sequence, and cooled to obtain a B1 grade cable material.

Citation Information

Patent Citations

  • High-speed low-shrink low-smoke zero-halogen tight-buffered material used for 4G optical cable and preparation method of high-speed low-shrink low-smoke zero-halogen tight-buffered material

    CN103897256A

  • B1-grade flame-retardant irradiation crosslinking low-smoke halogen-free insulated cable material and preparation method thereof

    CN109627567A

  • B1-grade special high-flame-retardant low-smoke halogen-free cable material and preparation method thereof

    CN111621085A

  • B1-grade low-smoke halogen-free cable oxygen barrier material and preparation method thereof

    CN112679837A

  • B1 flame-retardant cable sheath material and preparation method thereof

    CN113462063A

Cited By

  • Flame-retardant B1-level sheath material and application thereof in cable

    CN120383793A

  • A flame-retardant b1 class sheath material and its use in cables

    CN120383793B

  • Photovoltaic cable material, preparation method and application thereof

    CN120842732A

  • Vehicle-mounted flame-retardant communication optical cable and preparation method thereof

    CN120847959A